2003
DOI: 10.1080/10606820308263
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Signaling Mechanisms for Muscarinic Acetylcholine Receptors

Abstract: Signaling pathways for muscarinic acetylcholine receptors (mAChRs) include several enzymes and ion channels. Recent studies have revealed the importance of various isoforms of both alpha and betagamma subunits of G proteins in initiation of signaling as well as the role of the small monomeric G protein, Rho, in the activation of phospholipase D. Modulation of adenylyl cyclase activity by mAChRs appears more diverse as the interaction of various receptor subtypes with the many isoforms of the enzyme are studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
5

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(56 citation statements)
references
References 0 publications
0
51
0
5
Order By: Relevance
“…3;Liu et al, 2007;Park, Kim et al, 2003;Steger & Avery, 2004). All of them show high similarity in amino acid sequences to the known mammalian mAChRs M 1 , M 2 , M 3 , M 4 and M 5 , which are coupled to different G-proteins (Caulfield & Birdsall, 1998;Langmead et al, 2008;Lanzafame et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3;Liu et al, 2007;Park, Kim et al, 2003;Steger & Avery, 2004). All of them show high similarity in amino acid sequences to the known mammalian mAChRs M 1 , M 2 , M 3 , M 4 and M 5 , which are coupled to different G-proteins (Caulfield & Birdsall, 1998;Langmead et al, 2008;Lanzafame et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Muscarinic acetylcholine receptors are known to regulate numerous fundamental physiological processes including muscarinic actions of acetylcholine on peripheral effector tissues and a multitude of central sensory, vegetative and motor functions (Ellis et al, 2006;Erskine et al, 2004;Feiro & Gould, 2005;Lanzafame et al, 2003). Many studies have shown that central muscarinic receptors play an important role in the regulation of body temperature in mammals (Gomeza et al, 1999) and therefore are necessary for survival of these animals and humans at hot environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M2 and M4 mAChR couple preferentially to G i/9 affecting the adenylyl cyclase activity and inhibiting non-selective cation channels, transient receptor potential channels and potassium channels [20,21]. M1, M3 and M5 mAChR couple to G q/11 and increase intracellular calcium via generation of inositol 1,4,5-trisphosphate and 1,2-diacylglyerol [20,21]. The degradation of ACh into choline and acetate is catalyzed by the enzymes acetylcholinesterase (AChE) and the less specific butyrylcholinesterase.…”
Section: Introductionmentioning
confidence: 99%